Teachers and Students of Abu Isa Tirmidhi - Temirov Kabiljonovich (Penerbit Jurnal Indonesia, 2024)
In the article, the years of birth and death of Abu Isa Tirmidhi, when he went on a journey of knowledge and in which cities he visited, his famous teachers, the number of sheikhs and hadiths narrated the most in